2022
DOI: 10.1007/s10549-022-06830-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the intersectionality of race/ethnicity with rurality on breast cancer outcomes: SEER analysis, 2000–2016

Abstract: Purpose Disparities in breast cancer survival have been observed within marginalized racial/ethnic groups and within the rural–urban continuum for decades. We examined whether there were differences among the intersectionality of race/ethnicity and rural residence on breast cancer outcomes. Methods We performed a retrospective analysis among 739,448 breast cancer patients using Surveillance Epidemiology and End Results (SEER) 18 registries years 2000 throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…Moore et. al.’s study found that despite living in closer proximity to available healthcare services, increased odds of late-stage diagnosis, no receipt of treatment, and risk of breast cancer death were sustained for NH-AA women living in urban environments compared to rural NH-AA women [ 35 ]. One explanation to our findings may be a relative homogeneity in AL in AA women.…”
Section: Discussionmentioning
confidence: 99%
“…Moore et. al.’s study found that despite living in closer proximity to available healthcare services, increased odds of late-stage diagnosis, no receipt of treatment, and risk of breast cancer death were sustained for NH-AA women living in urban environments compared to rural NH-AA women [ 35 ]. One explanation to our findings may be a relative homogeneity in AL in AA women.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, patients who present at later stages may require more intense treatment regimens or may have less treatment options available to them compared with if they presented earlier. Six of the identified articles addressed this disparity, with 4 identifying a disparity [32][33][34][35] and 2 finding no relationship with the Hispanic population. 36,37 One of the identified studies, by Moore et al, 34 identified that regardless of rural versus urban location, patients with breast cancer that identified as Hispanic were more likely to present with latestage disease at diagnosis compared with non-hispanic white (NHW) patients (Hispanic-Urban: adjusted odds ratio [aOR] 1.25, Hispanic-Rural: aOR 1.75).…”
Section: Stage At Presentationmentioning
confidence: 99%
“…Five articles evaluated disparities regarding geography, including length of travel for treatment. Of the 5 articles identified, 4 identified a disparity for the Hispanic population 23,24,34,55 and 1 did not. 56 These articles found that regardless of location, Hispanic ethnicity was associated with less likelihood of receiving treatment, 23,34 that Hispanic patients had greater distance to travel to an RT treatment center, 55 and that Hispanic patients are less likely to travel far distances for treatment, worsening outcomes.…”
Section: Geographymentioning
confidence: 99%
“…Studies examining the impact of therapy duration on survival across these groups have identified significant differences in time to treatment initiation and survival [10,11]. Many factors affecting disparities in breast cancer have been identified, including social and health determinants along with individualized and tumor-related factors [12][13][14][15][16]. However, many studies have prioritized establishing association rather than examining the causal mechanisms underlying these associations [17,18], and many studies rely on cancer registry data, which often do not contain the information needed to assess such mechanisms.…”
Section: Introductionmentioning
confidence: 99%